Use of semantic analysis in ecological education - Z.Djurabaeva (Universitas Muhammadiyah Sidoarjo, 2019)
The present work deals with the use semantic analysis in ecological education. The article explores the use of semantic analysis to explain the meaning of lexical units related to ecology and the hyper-hyponymic relationship that occurs between lexemes.